Treasure in Literature and Culture. - Emig, Rainer (Regensburger Beiträge zur Gender-Forschung - Band 6., 2013)
Hauptbeschreibung Treasure and treasure hunting are vast themes in literature and culture, yet have so far not received much sustained and coherent academic interest. The present collection of essays approaches treasure and treasure hunts in literature and culture from the Renaissance to the present. It asks questions about the legal, social, and cultural role of treasure, especially in connection with its links with gender and sexuality. The essays of the collection deal with Renaissance documents and their depiction of legal struggles over treasure, Romantic conceptions of the sel.